Policing in the Australian Federation 1970–2010: A changed paradigm - Manison, Gary F. (Curtin University, 2015)
Australian policing before 1980 was a State responsibility, but it is now shared with the Commonwealth. Policing underwent a paradigm shift, driven by the Commonwealth and abnormally in the course of Australian federalism, consented to by the States. The hypothesis presented, based on the pragmatic federalism argument, is the paradigm shift occurred because the Commonwealth took on the role of principal problem-solver for new and expanding crime threats faced by all governments.